Neuroprotective Potential of Nutraceuticals in Managing Neurodegenerative Disorders (Asian Journal of Pharmaceutics (AJP), 2025)
Nutraceuticals, a broad category of food-derived products with possible health advantages, have attracted a lot ofinterest in the treatment of neurodegenerative diseases (NDDs), including multiple sclerosis, Parkinson’s disease,and Alzheimer’s disease. These disorders present considerable therapeutic challenges because of their complexetiology and limited treatment choices. They are characterized by progressive neuronal degeneration and relatedmotor and cognitive impairments. Because of their capacity to alter different biochemical and molecular pathwayslinked to neurodegeneration, nutraceuticals play a crucial role in managing non-alcoholic fatty liver disease NDD.Important processes include control of protein aggregation, antioxidative stress, anti-inflammatory effects, andmitochondrial protection. Pre-clinical and clinical research have demonstrated the potential neuroprotective effectsof compounds, such as omega-3 fatty acids, polyphenols (such as curcumin and resveratrol), and vitamins (such asVitamin E and Vitamin D). Furthermore, as a supplementary strategy to traditional treatments, nutraceuticals havethe ability to improve therapeutic results and halt the advancement of disease. Their accessibility, natural origin,and usually acceptable safety profile make them appealing candidates for long-term usage in the managementof NDDs notwithstanding its potential, variables, including bioavailability, dose optimization, and responsevariability, pose challenges to the therapeutic use of nutraceuticals in NDDs. To create uniform dosages, clarify themechanisms of action, and confirm their efficacy through well-planned clinical studies, more research is required.